Hubungan antara Usia, Lama Keluhan Nyeri Abdomen, Nilai Leukosit, dan Rasio Neutrofil Limfosit dengan Kejadian Apendisitis Akut Perforasi di RSUD Abdul Wahab Sjahranie Samarinda: Relationship between Age, Duration of Abdominal Pain, Leukocyte Value, and Neutrophil Lymphocyte Ratio with the Incidence of Acute Appendicitis Perforation at RSUD Abdul Wahab Sjahranie Samarinda - Nurnadhirah Mirantika; Danial Danial; Bambang Suprapto (Jurnal Sains dan Kesehatan, 2021)
Acute appendicitis is an infection that occurs in the appendix vermiformis or commonly known in the community with inflammation of the appendix. The incidence of appendicitis in the world is quite high and diagnosis is still a challenge in surgery. Delay in establishing a definite diagnosis of appendicitis has implications for suboptimal management and can lead to complications in the form of perforation. Perforation of the appendix vermiformis will result in peritonitis and can cause uncontrolled sepsis and intra-abdominal abscess. Age and delay in diagnosis are factors that play a role in the occurrence of perforation of the appendix vermiformis. The longer the complaint of abdominal pain experienced in acute appendicitis, the higher the possibility of perforation. Leukocyte count and lymphocyte neutrophil ratio is a laboratory test that can help diagnose acute appendicitis. The purpose of this study was to determine the relationship between age, duration of abdominal pain, leukocyte value, and neutrophil lymphocyte ratio with the incidence of acute appendicitis perforation. The design of this study uses a cross-sectional study with observational analytic methods. Data were taken from the medical records of patients with a diagnosis of acute appendicitis who received appendectomy at the Abdul Wahab Sjahranie Samarinda Regional General Hospital for the period 2018-2019 using purposive sampling technique and obtained 105 research samples. Bivariate analysis was performed using the chi-square test and fisher test if the expected count less than 5. The analysis results obtained a significant relationship between age (p=0,015), duration of abdominal pain (p=0,000), leukocyte value (p=0,049), and neutrophil lymphocyte ratio (p= 0,000) with the incidence of acute appendicitis perforation.